2014
DOI: 10.1111/jai.12458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tribulus terrestris extract on the survival and histopathology of Oreochromis mossambicus (Peters, 1852) fry before and after Streptococcus iniae infection

Abstract: SummaryThe aim of this study was to determine the effects of Tribulus terrestris extract (TT) on growth performance, disease resistance and histopathological changes in intestine and liver tissues of Oreochromis mossambicus (Peters, 1852) first-feeding fry before and after exposure to Streptococcus iniae. Five isonitrogenous and isocaloric diets were formulated to contain 0 (control), 200, 400, 600, and 800 mg kg À1 TT. After feeding for 45 days, fish were infected with S. iniae and mortalities recorded. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…It is stated that the first vaccination of Gambusia holbrooki in the freshwaters of Turkey as a precaution for the biological control of malaria against vector mosquitoes between 1920 and1929 (Walton et al, 2012). Even though Oreochromis mossambicus were used as a bioindicator organism in different types of studies including disease infection (Yılmaz et al, 2013;Gültepe et al, 2014;Yilmaz et al, 2014) in the universities of Turkey by making its culture, the species has not been recorded in open freshwater systems in Turkish.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that the first vaccination of Gambusia holbrooki in the freshwaters of Turkey as a precaution for the biological control of malaria against vector mosquitoes between 1920 and1929 (Walton et al, 2012). Even though Oreochromis mossambicus were used as a bioindicator organism in different types of studies including disease infection (Yılmaz et al, 2013;Gültepe et al, 2014;Yilmaz et al, 2014) in the universities of Turkey by making its culture, the species has not been recorded in open freshwater systems in Turkish.…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al 191 found that TT extract had a potential for symptom relief in Mozambique tilapia fish ( Oreochromis mossambicus ) suffering from liver disorder after S. iniae infection. They suggested that TT extracts improved nutrition and could be used as an alternative instead of antibiotics for streptococcus infections in tilapia fish.…”
Section: Pharmacological Activity Of Herba T Terrestrismentioning
confidence: 99%
“…Diseases lead to a reduced commercial value of fish, increased mortality, and decreased growth rates . There are pathogens that can affect aquaculture such as Aeromonas hydrophila ( A. hydrophila ), Edwardsiella tarda ( E. tarda ), , and Streptococcus iniae ( S. iniae ), , causing mainly skin ulceration, hemorrhagic septicemia, internal hemorrhage, pale gills, lateral line necrosis, lethargy, exophthalmia, and anorexia. …”
Section: Introductionmentioning
confidence: 99%